Flexible, Permeable, and Recyclable Liquid‐Metal‐Based Transient Circuit Enables Contact/Noncontact Sensing for Wearable Human–Machine Interaction. Issue 4 (22nd February 2023) - Zheng, Kai; Gu, Fan; Wei, Hongjin; Zhang, Lijie; Chen, Xi'an; Jin, Huile; Pan, Shuang; Chen, Yihuang; Wang, Shun
Abstract: The past several years have witnessed a rapid development of intelligent wearable devices. However, despite the splendid advances, the creation of flexible human–machine interfaces that synchronously possess multiple sensing capabilities, wearability, accurate responsivity, sensitive detectivity, and fast recyclability remains a substantial challenge. Herein, a convenient yet robust strategy is reported to craft flexible transient circuits via stencil printing liquid metal conductor on the water‐soluble electrospun film for human–machine interaction. Due to the inherent liquid conductor within porous substrate, the circuits feature high‐resolution, customized patterning viability, attractive permeability, excellent electroconductivity, and superior mechanical stability. More importantly, such circuits display appealing noncontact proximity capabilities while maintaining compelling tactile sensing performance, which is unattainable by traditional systems with compromised contact sensing. As such, the flexible circuit is utilized as wearable sensors with practical multifunctionality, including information transfer, smart identification, and trajectory monitoring. Furthermore, an intelligent human–machine interface composed of the flexible sensors is fabricated to realize specific goals such as wireless object control and overload alarm. The transient circuits are quickly and efficiently recycled toward high economic and environmental values. This work opens vast possibilities of generating high‐quality flexible and transient electronics for advanced applications in soft and intelligent systems. Abstract : High‐quality flexible and transient electronics with compelling contact/noncontact sensing capabilities, sensitive detectivity, superior mechanical stability, excellent electroconductivity, and convenient recyclability are realized via patterning liquid metal conductor on electrospun polyvinyl alcohol substrate for human–machine interaction, which can be readily extended to a rich diversity of conductive liquid metal, recyclable polymers, and functional patterned electronics for advanced wearable and smart devices.